CONCEPTUAL LEARNING MODEL WITH MARIND CULTURE BASED FOR ELEMENTARY SCHOOL IN KAIBURSE MERAUKE - Seli Marlina Radja Leba; Dian Mayasari; Irmawaty Natsir (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
Each region has a cultural heritage that has been passed down for generations, even in areas within one country have various kinds of cultural heritage. One of the areas in Indonesia that has a cultural heritage is Merauke Regency which is inhabited by the Malind Tribe. This study aims to apply real experiences that can be found in the Malind (Papua) tribe as material in curriculum development that can be applied in the South Papua region. This research was conducted in a village located in Kaiburse, Merauke Regency, which is inhabited by the Malind people. This research is a descriptive research with a qualitative approach. Researchers continuously participate actively in the field by recording and analyzing and representing all findings found in the field. The approach used in order to analyze in depth all forms of cultural heritage values found in the indigenous people of the Marind tribe who inhabit Kaiburse Village. The real experience gained based on the results of observations, interviews in the field and documentation during the research that is then carried out is data triangulation. This research produces an explanation of local wisdom in mathematics material. This research can be the main source of the government to integrate local wisdom in learning in schools